2006
DOI: 10.1074/jbc.m606402200
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Induce Ca2+ Release from Both the Endoplasmic Reticulum and Acidic Intracellular Calcium Stores through Activation of Inositol Trisphosphate Receptors and Ryanodine Receptors

Abstract: Gallstones can cause acute pancreatitis, an often fatal disease in which the pancreas digests itself. This is probably because of biliary reflux into the pancreatic duct and subsequent bile acid action on the acinar cells. Because Ca 2؉ toxicity is important for the cellular damage in pancreatitis, we have studied the mechanisms by which the bile acid taurolithocholic acid 3-sulfate (TLC-S) liberates Ca 2؉ . Using two-photon plasma membrane permeabilization and measurement of [Ca 2؉ ] inside intracellular stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
138
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 50 publications
6
138
0
2
Order By: Relevance
“…Our previous studies of 2-photon permeabilized acinar cells (21,22) showed the existence of 2 separate Ca 2ϩ stores, namely the ER and an acidic store. The ER maintains a high Ca 2ϩ concentration by action of a Ca 2ϩ pump, which can be specifically inhibited by TG (25) thereby depleting the ER of Ca 2ϩ due to leaks in the ER membrane (3,26).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Our previous studies of 2-photon permeabilized acinar cells (21,22) showed the existence of 2 separate Ca 2ϩ stores, namely the ER and an acidic store. The ER maintains a high Ca 2ϩ concentration by action of a Ca 2ϩ pump, which can be specifically inhibited by TG (25) thereby depleting the ER of Ca 2ϩ due to leaks in the ER membrane (3,26).…”
Section: Resultsmentioning
confidence: 97%
“…Although the endoplasmic reticulum (ER) is the principal source of Ca 2ϩ released from internal stores in response to neurotransmitter or hormonal stimulation (3,15,16), Ca 2ϩ can also be liberated from acid stores (3,15,(17)(18)(19)(20)(21)(22). Several Ca 2ϩ -liberating agents release Ca 2ϩ from both thapsigargin (TG)-sensitive and bafilomycin (Baf)-sensitive acidic stores (21,22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown previously that the Cl -/HCO 3 -exchanger SLC26A3 and NHE3 are inhibited by the pathological increase of intracellular Ca 2+ [6,26]. In our experiments, CDC induced a dose- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 the release from the ER via IP 3 R and/or RyR or Ca 2+ entry from the extracellular space [32,14,13] [26].…”
Section: Discussionmentioning
confidence: 99%